Nucleoli cytomorphology in cutaneous melanoma cells - a new prognostic approach to an old concept - Piotr Donizy; Przemyslaw Biecek; Agnieszka Halon; Adam Maciejczyk; Rafal Matkowski (BMC, 2017)
Abstract Background The nucleolus is an organelle that is an ultrastructural element of the cell nucleus observed in H&E staining as a roundish body stained with eosin due to its high protein content. Changes in the nucleoli cytomorphology were one of the first histopathological characteristics of malignant tumors. The aim of this study was to assess the relationship between the cytomorphological characteristics of nucleoli and detailed clinicopathological parameters of melanoma patients. Moreover, we analyzed the correlation between cytomorphological parameters of nucleoli and immunoreactivity of selected proteins responsible for, among others, regulation of epithelial-mesenchymal transition (SPARC, N-cadherin), cell adhesion and motility (ALCAM, ADAM-10), mitotic divisions (PLK1), cellular survival (FOXP1) and the functioning of Golgi apparatus (GOLPH3, GP73). Methods Three characteristics of nucleoli - presence, size and number - of cancer cells were assessed in H&E-stained slides of 96 formalin-fixed paraffin-embedded primary cutaneous melanoma tissue specimens. The results were correlated with classical clinicopathological features and patient survival. Immunohistochemical analysis of the above mentioned proteins was described in details in previous studies. Results Higher prevalence and size of nucleoli were associated with thicker and mitogenic tumors. All three nucleolar characteristics were related to the presence of ulceration. Moreover, microsatellitosis was strongly correlated with the presence of macronucleoli and polynucleolization (presence of two or more nucleoli). Lack of immunologic response manifested as no TILs in primary tumor was associated with high prevalence of melanoma cells with distinct nucleoli. Interestingly, in nodular melanoma a higher percentage of melanoma cells with prominent nucleoli was observed. In Kaplan-Meier analysis, increased prevalence and amount, but not size of nucleoli, were connected with shorter cancer-specific and disease-free survival. Conclusion (1) High representation of cancer cells with distinct nucleoli, greater size and number of nucleoli per cell are characteristics of aggressive phenotype of melanoma; (2) higher prevalence and size of nucleoli are potential measures of cell kinetics that are strictly correlated with high mitotic rate; and (3) high prevalence of cancer cells with distinct nucleoli and presence of melanocytes with multiple nucleoli are features associated with unfavorable prognosis in patients with cutaneous melanoma.